Biotechnological production and application of fructooligosaccharides - Flores-Maltos, D. A. (2016)
Currently, prebiotics are all carbohydrates of relatively short chain length. An important group is the fructooligosaccharides, which are a special kind of prebiotics associated to their selective stimulation of the activity of certain groups of colonic bacteria that have a positive and beneficial effect on intestinal microbiota, reducing incidence of gastrointestinal infections, respiratory and also possessing a recognized bifidogenic effect. Traditionally, these prebiotic compounds have been obtained through extraction processes from some plants, as well as through enzymatic hydrolysis of sucrose. However, different fermentative methods have also been proposed for the production of fructooligosaccharides, such as solid-state fermentation utilizing various agroindustrial by-products. By optimizing the culture parameters, fructooligosaccharides yields and productivity can be improved. The use of immobilized enzymes and cells has also been proposed as being an effective and economic method for large-scale production of fructooligosaccharides. This paper is an overview on the results of recent studies on fructooligosacharides biosynthesis, physicochemical properties, sources, biotechnological production and applications.